2018
DOI: 10.1096/fj.201800784r
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of G0/G1 switch gene 2 (G0S2) reduced abdominal fat deposition and altered fatty acid composition in chicken

Abstract: Chicken as a food source is one of the most widespread domestic animals, and it has been used extensively as a research model. The clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (Cas9) system is the most efficient and reliable tool for precise genome-targeted modification and has generated considerable excitement for industrial applications, as well as biologic science. Unlike in mammals, germline-transmittable primordial germ cells (PGCs) in chicken were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
(45 reference statements)
0
41
0
Order By: Relevance
“…Interestingly, these G0S2 knockout chickens did not show any phenotypic differences compared to wild-type chickens (Park et al, 2019). This G0S2 knockout line is expected to offer considerable insight into the mechanisms of fat metabolism in chickens, which could be useful for industrial applications by enabling greater control of energy balance.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Interestingly, these G0S2 knockout chickens did not show any phenotypic differences compared to wild-type chickens (Park et al, 2019). This G0S2 knockout line is expected to offer considerable insight into the mechanisms of fat metabolism in chickens, which could be useful for industrial applications by enabling greater control of energy balance.…”
mentioning
confidence: 92%
“…The following year, Park et al (2014) reported the creation of an ovalbumin gene knockout chicken using the TALEN gene-editing platform (Park et al, 2014). More recently, there have been a handful of reports describing the generation of targeted mutants in chicken via the CRISPR/Cas9 system (Dimitrov et al, 2016;Oishi et al, 2016;Oishi et al, 2018;Park et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional research is required because it is not clear how miR-146b-5p affects myogenic differentiation, and there are no reports addressing its effects on chicken myogenesis. Thus, in this study, we designed and constructed a miRNA expression vector system to overexpress miR-146b-5p in pCM cells using the piggyBac transposon system, which previous studies have demonstrated to be an e cient transgene delivery system [22,23]. miR-146b-5p increased proliferation and decreased differentiation by regulating genes related to the cell cycle in chicken myoblasts.…”
Section: Introductionmentioning
confidence: 99%